2019
DOI: 10.1002/slct.201903191
|View full text |Cite
|
Sign up to set email alerts
|

rGO‐SO3H Catalysed Green Synthesis of Fluoro‐Substituted Aminomethylene Bisphosphonates and their Anticancer, Molecular Docking studies

Abstract: A facile and green synthetic protocol was aimed for the synthesis of aminomethylene bisphosphonates via one-pot reaction of fluorine bearing anilines, triethyl orthoformate and dialkyl phosphite in presence of rGO-SO 3 H as catalyst under microwave irradiation and solvent-free conditions. All the title compounds were evaluated for their anticancer activity against human breast cancer cell lines (MCF-7) by MTT assay method using exemestane as standard drug. Molecular docking studies were carried out against Hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Studies showed that the growth of the tumor can be effectively inhibited by MIF inhibitors and the inhibitory effect can be significantly enhanced by adding fluorine atoms (Dziedzic et al 2015 ). Similarly, other fluorinated compounds also exhibited stronger inhibitory effects than non-fluorinated compounds for distinct tumor cells, such as fluorinated green tea polyphenols, fluorinated largazole, fluorinated 4-thiazolidinone, fluorinated griseofulvin, fluorinated l -threonine, fluorinated aminophosphonite, and fluorinated docetaxel (Zhang et al 2019a ) (Stadlbauer et al 2018 ) (Makki et al 2019 ; Olgun 2019 ; Paguigan et al 2017 ; Sudileti et al 2019 ; Tang et al 2016 ). These results indicated that the incorporation of fluorine-substituted fragments into the inhibitor is an effective means to enhance the therapeutic effect of tumors.…”
Section: Applications Of Fluorinated Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies showed that the growth of the tumor can be effectively inhibited by MIF inhibitors and the inhibitory effect can be significantly enhanced by adding fluorine atoms (Dziedzic et al 2015 ). Similarly, other fluorinated compounds also exhibited stronger inhibitory effects than non-fluorinated compounds for distinct tumor cells, such as fluorinated green tea polyphenols, fluorinated largazole, fluorinated 4-thiazolidinone, fluorinated griseofulvin, fluorinated l -threonine, fluorinated aminophosphonite, and fluorinated docetaxel (Zhang et al 2019a ) (Stadlbauer et al 2018 ) (Makki et al 2019 ; Olgun 2019 ; Paguigan et al 2017 ; Sudileti et al 2019 ; Tang et al 2016 ). These results indicated that the incorporation of fluorine-substituted fragments into the inhibitor is an effective means to enhance the therapeutic effect of tumors.…”
Section: Applications Of Fluorinated Compoundsmentioning
confidence: 99%
“…The development of novel pharmaceutical intermediates has become more and more urgent and necessary. Selective fluorination is an effective strategy to improve pharmaceutical efficacy, half-life, lipophilicity, absorption rate, and the permeability of cell membranes (Sudileti et al 2019 ; Zhou et al 2016 ). Therefore, the exploration has never stopped for the role of fluorine in drug design since the first fluorinated drug (9α-fluoro-substituted corticosteroid fludrocortisone) was approved in the 1950s (Fried and Sabo 1954 ).…”
Section: Applications Of Fluorinated Compoundsmentioning
confidence: 99%
“…However, an additional bioactive functionalized moiety in the bisphosphonate molecule such as 1H‐indazole, 1H‐pyrazolo[3,4‐b]pyridine and 1H‐pyrazolo[3,4‐b]quinolone, [22] 2‐amino‐ benzothiazole, [23] nitrogen and sulfur, [24] sulfonylamino, [25] fluoro‐substituted amine, [26] pyrazole, [27] acrylamide‐derived monomer, [28] amino acid, [29] hyaluronic acid, [30] and ethylidene‐pyridine bisphosphonate polyoxovanadates complexes, [31] give new derivatives for this class of molecules and offer promising and remarkable biological and industrial applications.…”
Section: Introductionmentioning
confidence: 99%
“…[11] Furthermore, these compounds have gained considerable attention in the field of medicinal chemistry due to their role in many biological activities, including anti-inflammatory, [12] antioxidant, [13] antifungal, [14,15] antibacterial and antiviral, [16] anticancer, [17] antiparasitic, [18] herbicidal, [19] as well as chelating agents. [20,21] However, an additional bioactive functionalized moiety in the bisphosphonate molecule such as 1H-indazole, 1Hpyrazolo [3,4-b]pyridine and 1H-pyrazolo [3,4-b]quinolone, [22] 2amino-benzothiazole, [23] nitrogen and sulfur, [24] sulfonylamino, [25] fluoro-substituted amine, [26] pyrazole, [27] acrylamide-derived monomer, [28] amino acid, [29] hyaluronic acid, [30] and ethylidene-pyridine bisphosphonate polyoxovanadates complexes, [31] give new derivatives for this class of molecules and offer promising and remarkable biological and industrial applications.…”
Section: Introductionmentioning
confidence: 99%
“…For example, tetramethyl bisphosphonate 2 displayed antioxidant activity comparable with that of ascorbic acid, and higher antifungal activity than that of voriconazole . Tetraethyl bisphosphonate 3 showed superior antiproliferation activities in vitro than the anticancer drug Exemestane . Compound 4 is a new type of human geranylgeranyl pyrophosphate synthase (hGGPPS) inhibitors …”
Section: Introductionmentioning
confidence: 99%